Cruelty against domestic animals: a comparative study of the legal protection in Malaysia with U.K / Marina Malim ... [et al.] - Malim, Marina; Kamal, Darlina; Jabar, Noor Faiz; Idris, Nur Fadhilah (2006)
This research is conducted for the purpose of reviewing the current law on the legal protection for domestic animal in Malaysia. Besides that, it is conducted to provide a better understanding and awareness regarding the legal protection for cruelty against domestic animals in Malaysia in comparison with the UK animal legal protection. This research would be conducted through library research that includes primary and secondary sources as well as interview. The importance of the study is to provide useful legal data and information.